Landaeta Lardones, P., y Arias Krause, J. I. “La interpretación política de la tragedia griega en Hegel.” (2015)
Landaeta Lardones, P., y Arias Krause, J. I. “La interpretación política de la tragedia griega en Hegel.” Co-herencia 10.19 (2013): 113-133.